Influence of negative electronic word-of-mouth on consumer's intention to switch mobile service provider in Malaysia - Nadarajan, Geetha (2018)
Consumer decisions are increasingly influenced by word-of-mouth of friends, family and other consumers. With the advent of Web 2.0, much of the word-of-mouth is online and 65% consumers learn about products or services of interest online and a whopping 50% use social media to air their grouses or complaints on service providers particularly mobile service provider (Nielsen, 2014). However, given the importance of electronic word-of-mouth (eWOM), there is lack of studies on how eWOM from online communities influence mobile switching. This study explored the influence of negative electronic word-of-mouth (eWOM) on mobile consumer switching. Negative eWOM is online consumer’s expression of an unfavourable product or service experience and recommendation not to buy (Luo, 2009). Using convergent design mixed methods, qualitative phase involved the netnography technique where the negative eWOM and its related discussion thread of 537 eWOM in an online community on mobile consumer switching was collected and analyzed. Thematic analysis revealed that there were six (6) main elements in the negative eWOM including consumer environment, mobile experience/knowledege, tangible mobile benefits and costs, affects and agree or disagree behaviors to the negative eWOM. Quantitative phase analysed the influence of the same negative eWOM on consumer’s switching where 585 valid responses were collected via an electronic survey instrument distributed to public. Regression and multiple comparison test results indicate given varying consumer affects, consumer behaviour towards the negative eWOM has significant influence on consumer switching intentions. In summary, the analysis of negative eWOM showed that in a token based mobile consumption setting like Malaysian telecommunications industry, consumer awareness of selective treatment by service providers through negative word-of-mouth alights sentiments which increases the likelihood to switch service providers. The findings of this research provide important implications for the understanding of mobile consumer switching which could not be explained based on price, network and service alone.